Investigating circulatory microRNA expression profiles in Egyptian patients with HCV induced hepatocellular carcinoma - Al Anany, Amany (AUC Knowledge Fountain, 2018)
Hepatitis C virus (HCV) infection is a serious health challenge affecting over 185 million individuals globally. Egypt has the highest rate for chronic HCV infection worldwide. Recent studies have shown that from 10%-30% of HCV infected individuals would progress to more deteriorating conditions such as cirrhosis and/or hepatocellular carcinoma (HCC). Current biomarkers for HCC diagnosis are lacking both sensitivity and specificity. As a result there is demand to develop reliable biomarkers that are sensitive, specific and non-invasive for early diagnosis and rapid intervention of HCC to increase the survival rate of patients. Recently, circulatory miRNAs have drawn great attention as promising non-invasive biomarkers for various diseases. They are highly stable in blood and their expression profiles reflect disease progression and/or drug response status. Besides, a number of miRNAs were found to be commonly dysregulated in HCC. In this study, we investigated mi-RNA expression profile from the plasma of Egyptian patients with chronic hepatitis C, cirrhosis and HCV associated HCC compared with healthy control. We aimed to assess the diagnostic potential of the selected miRNAs to differentiate between healthy, HCV and HCV associated disorders (cirrhosis and HCC). In addition to studying the expression pattern in the different studied stages. Using real time PCR, we compared the levels of circulating mir-122, miR-21 and miR-155 in plasma from healthy control (n=40), cirrhosis (n=39) and HCC (n=40) to CHC (n=37). Synthetic miR-39 was spiked in the samples to be used as a normalizing control for the samples. Plasma miR-122 was significantly up-regulated iii in HCC than in the three other categories (P<0.001). The plasma level of miR-122 in HCC patients was significantly higher than healthy control and cirrhotic patients (P = 0.002 and P<0.001, respectively). The plasma level of miR-21 was significantly upregulated in HCC compared to cirrhotic patients (P=0.03). Although Control and HCC in mir-21 increased by 3.52 and 6 log2 scale respectively, they were in marginal insignificance (p=0.093) that might be due to limited number of samples used in this study. There had been no significant dys-regulation in the expression levels of miR155 between the 4 categories. Receiver operating characteristic curves’ analysis revealed that miR-122 differentiated HCC patients from healthy control with a specificity and sensitivity 57.50% and 65.52% respectively (at a cutoff >1.86). To discriminate cirrhotic patients from HCC subjects, a specificity and sensitivity of 61.54% and 1.43% (at a cutoff> 0.43) were determined. Additionally, analyzing ROC curve indicated that miR-21 differentiated HCC patients from cirrhotic patients with best sensitivity and specificity 72.97% and 50% (at a cutoff >-0.43). In conclusion, plasma miR-122 and miR-21 may be further investigated as potential markers for HCV associated HCC.